ANALYSIS OF SEMANTIC PROSODY IN THE COLLOCATION WORDS OF "SOCIAL DISTANCING" AND "PHYSICAL DISTANCING" - Audina Oktaviana (Lire Journal (Journal of Linguistics and Literature), 2020)
Abstract This study discusses the collocation of the words 'social distancing' and 'physical distancing'. Both of these phrases are new words that emerge during the current condition of COVID-19, which has a general definition of interference to prevent transmission of COVID-19 to become more widespread. 'Social distancing' and 'physical distancing', based on the frequency of the use of these two words, were identified as the significant collocates in reference to the frequency of word tokens. This study proves the collocation of negative and positive meanings of the words 'social distancing' and 'physical distancing'. This study uses qualitative methods with data sources using Corpora COVID-19 on the sketch engine, through the corpus approach. To find the collocation of the two phrases, a lot of COVID-19 journals were searched. The results of the analysis are the word tokens from the collocation of words that follow the phrase 'social distancing' as many as 2,678 (9.54 per million) words. Meanwhile, the collocation of the phrase 'physical distancing' shows results of 51 (0.18 per million) words. This shows that usage in COVID-19 data journals in the sketch engine is more in the phrase 'social distancing' than 'physical distancing'. Based on the semantic prosody collocation, words that follow ‘social distancing’ tend to be collocated (positive and negative), then this results in neutral. Meanwhile, words that follow ‘physical distancing’ have a positive tendency. Keywords: collocation, physical distancing, semantic prosody, social distancing.